Night train to Munich - Wellesley, Gordon (The Criterion collection, 2010)
Takes viewers on a World War II era journey from Prague to England to the Swiss Alps, as Nazis pursue a Czech scientist and his daughter who are being aided by a debonair British undercover agent.